Islamic Jerusalem and its Christians : a history of tolerance and tensions - Abu-Munshar, Maher Y. (I.B. Tauris, 2013)
Islamic Jerusalem has a special place in hearts of three monotheistic religions. This book looks at historical events during the time of two key figures in the history of Islam: Caliph Umar Ibn Al-Khattab, who played an important role in the birth and spread of Islam and Sultan Salah al-Din, the legendary 'Saladdin' of Western Crusader lore